The Veterinary Medicine career, University Centrooccidental “Lisandro Alvarado” (UCLA), under the regional accreditation system university of careers MERCOSUR. (Gaceta de Ciencias Veterinarias, 2016)
It set suficient, reliable and transparent information , which allowed making a judgment about the quality criteria ARCO SUR compliance degree and recommendations for decision-making on improving the quality of Veterinary Medicine career. The self-assessment notes set actions for the UCLA Veterinary Medicine career, under Regional Accreditation System University Degree MERCOSUR seeking accreditation in ARCU SUR. For this, Its reported back on the compliance degree with quality criteria set by the system. The report was structured according to following dimensions: Institutional Context, Academic Project, University Population, and Infrastructure.
Keywords: Accreditation system